Interplay of Thyroid hormones, Nitric oxide and Nitric oxide synthase in Potentiating the Breast Cancer metastasis - Maira Mahmood Bokhari, Huma Sattar, Arif Malik, Rukhshan Khurshid, Faiza Aamir, Aamenah Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Thyroid hormones are able to induce proliferation of breast cancer(BC) cells and these growth promoting effects were similar to estrogen suggesting a significant small talk between the two hormones. Aims and Objectives: A cross sectional study is designed to see the Interplay of thyroid hormones (fT3 and fT4), nitric oxide and nitric oxide synthase in potentiating BC metastasis. Material and Methods: 288 consented breast cancer patients within the age range of 30-60 years and 100 age matched healthy controls were included in the study. Estimation of thyroid hormones including fT3 and fT4, vascular endothelial growth factor (VEGF), Matrix Metalloprotienase 9 (MMP-9) and inducible nitric oxide synthase (iNOS) was carried out by ELISA. Data was analyzed by SPSS 20.0. Variables of subjects and patients was compared by student ‘t’ test. The Correlation analysis was carried out by Pearson Correlation Coefficient. . Results: Increased levels of T3, T4, VEGF,NO, NOS AND MMP 9 were observed in subjects as compared to controls. Correlation coefficient showed positive correlation between fT3,NO and NOS. On the other hand, negative correlation was observed between fT4, NO and NOS. Conclusion: This study indicates a probable relationship between hyperthyroidism, NO,NOS,VEGF in the progression and metastasis of BC.